Weber B Distal Fibular Fracture Diagnosed by Point-of-care Ultrasound - Makinen, James (Clin Pract Cases Emerg Med, 2016)
We report the case of a 45-year-old woman who presented to the emergency department (ED) after an acute ankle inversion injury. After history and physical exam suggested a potential fracture, point-of-care ultrasound (POCUS) demonstrated a cortical defect of the distal fibula, consistent with fracture. Plain radiography failed to demonstrate a fracture. Later, the fracture was identified as a Weber B distal fibular fracture by stress-view radiography. This case reviews the evaluation of acute ankle injuries in the ED and the utility of POCUS as a supplemental imaging modality in the evaluation of ankle fracture.